The Urgency of Islamic Counseling Guidance in Mental Health Development For Students at Mts - Saiful Akhyar Lubis; Abdurrahman Abdurrahman; Dwy Jaya Maria Ulfah (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2022)
There are so many cases of delinquency that occur to students that they need counseling guidance which is an effort to help individuals achieve optimal development. This study aims to analyze: the mental health conditions of students at MTs Aisyiyah Binjai, implementation of Islamic counseling guidance at MTs Aisyiyah Binjai, the concept of Islamic counseling guidance in mental health development at MTs Aisyiyah Binjai, mental health maintenance efforts at MTs Aisyiyah Binjai. This study uses a qualitative method, using a naturalistic phenomenological research approach. Collecting data using interviews, observations, and documentation studies. The informants in this study were the head of MTs Aisyiyah Binjai, counselors (BK teachers) at MTs Aisyiyah Binjai, parents of students, and students at MTs Aisyiyah Binjai. The data collected through these various techniques are examined and carried out with data reduction, data presentation, and verification or concluding. There are four findings in this study: 1) There is a social gap, from the school to students mistreated between students whose economy is middle to upper and students whose economy is middle to lower, 2) lack of approach between teachers and students. 3) lack of respect between teachers and students.